Arbuscular Mycorrhizal Symbiosis as a Promising Resource for Improving Berry Quality in Grapevines Under Changing Environments - Torres, Nazareth; Antolín, M. Carmen; Goicoechea, Nieves (Frontiers in Plant Science, 2018)
Climate change and their resulting impacts are becoming a concern for winegrowers due to the high socioeconomic relevance of the winemaking sector worldwide. In fact, the projected climate change is expected to have detrimental impacts on the yield of grapevines, as well as on the quality and properties of grapes and wine. It is well known that arbuscular mycorrhizal fungi (AMF) can improve the nutritional quality of edible parts of crops and play essential roles in the maintenance of host plant fitness under stressed environments, including grapevines. The future scenarios of climate change may also modify the diversity and the growth of AMF in soils as well as the functionality of the mycorrhizal symbiosis. In this review, we summarize recent research progress on the effects of climate change on grapevine metabolism, paying special attention to the secondary compounds involved in the organoleptic properties of grapes and wines and to the levels of the phytohormones implied in the control of berry development and fruit ripening. In this context, the potential role of AMF for maintaining fruit quality in future climate change scenarios is discussed.